Peran Metodologi Pengembangan Dakwah dalam Membina Akhlak Jamaah: Analisis pada Majelis Sholawat Nurul Musthofa Kecamatan Sumberjambe Kabupaten Jember - Muhammad Ferdi Hamzah Agus Maulana; Ani Qotuz Zuhro’ Fitriana (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Da’wah is a fundamental activity in Islam that serves not only as the delivery of religious messages but also as a means of community development and social transformation. In Indonesia, however, many da’wah practices remain confined to normative-textual approaches that fail to adequately address contemporary social dynamics. This research explores the role of da’wah methodology in fostering moral development among the congregation of Majelis Sholawat Nurul Musthofa, located in Sumberjambe District, Jember Regency. Employing a qualitative case study approach, the study involves interviews, observations, and documentation with the kyai, administrators, and members. Findings indicate that da’wah activities emphasize the bil-hal (exemplary) approach, direct mentoring, and community engagement. The kyai’s exemplary behavior and gentle communication are key factors in shaping the moral transformation of the congregation. This study concludes that da’wah methodologies grounded in personal example, compassion, and cultural adaptation are effective in strengthening the spiritual and ethical values of the jamaah.